Effect of Tree Age on Seed and Seedling Quality in Acacia nilotica - Suresh, K. K.; Jambulingam, R.; Sekar, I. (Indian Forester, 2001)
Quality seeds play an important role in the establishment and productivity of forest plantation. Among various factors which tells upon the quality of seeds, the tree age in also one. Studies on the effect of tree age on seed and seedling quality in A. nilotica revealed that seeds collected from trees more than eight year old gave better quality seed with high 100 seed weight, germination and germination values. These seed in turn gave healthy seedlings in the nursery with higher values of shoot/root length, root/shoot ratio and dry matter production. Hence, in collecting seeds for nursery raising in this species tree of more than eight years should be chosen.